Gestión del conocimiento en la educación ambiental : Estudio de casoen el programa de educación ambiental de la universidad de São Paulo Brasil - Escrivão, Giovana [UNESP]; Nagano, Marcelo Seido (My University, 2012)
The objective of this study was to analyze and to describe the process of knowledge creation in an environmental education program. The research can be defined as a case study, because a thorough study of the characteristics of an environmental education program at a public university in Brazil was carried out. The study had a descriptive character; it observed, ordered and recorded data and behavior, explaining and interpreting facts without manipulating them, using a method of qualitative data collection, the interview. The method of data analysis used was content analysis. At the end good practices for environmental education programs are suggested.
Knowledge management in environmental education : A case study in the environmental education program at the university of são paulo , Brazil